Separation And Utilization Of Household Waste Through Android-Based Online Massage Gateway Assistant - Zakhiyatul Galuh Nafisah; M. Ali Sodik (Universitas STRADA Indonesia, 2021)
Garbage is a factual problem faced by urban areas in Indonesia. Overcoming the waste problem is not only the responsibility of the government, but there must be awareness and participation from the community. Organic waste is waste that can decompose or can be decomposed again with the help of other bacteria. Inorganic waste (dry waste), namely waste that does not decompose easily, such as plastic food packaging containers, paper, plastic toys and so on. The purpose is to find out the sorting and utilization of household waste through an Android-Based Online Massage Geteway companion. The research method that the researcher uses is quantitative research. The research data used primary data that was taken directly by filling out the google form to housewives in Bujel Village from January 2021 to February 2021. The sampling technique used Accidental Sampling. The total sample of this study was 73 respondents. Characteristics of respondents based on age 34-44 years, as many as 33 respondents (45.2%). Meanwhile, the characteristics of respondents based on their education history were mostly high school as many as 29 respondents (39.7%). Before sorting waste with sufficient category, 34 respondents (46.6%). Meanwhile, before utilization with sufficient category, 47 respondents (64.4%). It is known that the respondents already know the method of sorting with a good category of 43 respondents (58.9%). And how to use the category enough 42 respondents (57.5%). Based on the results of the WilcoxonTest statistical test analyst above, it is known that Asymp.Sig. (2-tailed) is worth 0.00 because the value of 0.00 is smaller than <0.05, it can be concluded that